Transgenic mouse model for the study of enterovirus 71 neuropathogenesis - Fujii, Ken; Nagata, Noriyo; Sato, Yuko; Ong, Kien Chai; Wong, Kum Thong; Yamayoshi, Seiya; Shimanuki, Midori; Shitara, Hiroshi; Taya, Choji; Koike, Satoshi (Proceedings of the National Academy of Sciences - PNAS, 2013)
Enterovirus 71 (EV71) typically causes mild hand-foot-and-mouth disease in children, but it can also cause severe neurological disease. Recently, epidemic outbreaks of EV71 with significant mortality have been reported in the Asia-Pacific region, and EV71 infection has become a serious public health concern worldwide. However, there is little information available concerning EV71 neuropathogenesis, and no vaccines or anti-EV71 drugs have been developed. Previous studies of this disease have used monkeys and neonatal mice that are susceptible to some EV71 strains as models. The monkey model is problematic for ethical and economical reasons, and mice that are more than a few weeks old lose their susceptibility to EV71. Thus, the development of an appropriate small animal model would greatly contribute to the study of this disease. Mice lack EV71 susceptibility due to the absence of a receptor for this virus. Previously, we identified the human scavenger receptor class B, member 2 (hSCARB2) as a cellular receptor for EV71. In the current study, we generated a transgenic (Tg) mouse expressing hSCARB2 with an expression profile similar to that in humans. Tg mice infected with EV71 exhibited ataxia, paralysis, and death. The most severely affected cells were neurons in the spinal cord, brainstem, cerebellum, hypothalamus, thalamus, and cerebrum. The pathological features in these Tg mice were generally similar to those of EV71 encephalomyelitis in humans and experimentally infected monkeys. These results suggest that this Tg mouse could represent a useful animal model for the study of EV71 infection.